(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
Biometric recognition is a means of identification in which natural human endowment is used. Fingerprint, Iris, Face, DNA are examples of biometrics. Algorithms have been developed to recognize and identify each natural human endowment which in turn can be used to identify every human being. The aim of this study is to develop a safe which can only be accessed using Fingerprint with vibration sensor thereby improving the safety and security of traditional locks using key and padlock. This system ensures that only users whose fingerprint has been enrolled on the fingerprint sensor memory can access the Safe. Fingerprint Biometric among other biometrics can deliver high level of security which eradicates the need to remember PINs, passwords or the necessity of carrying keys/cards and identity proof. The system makes use of an Arduino UNO microcontroller which controls and connect the necessary hardware required for locking and unlocking the safe. The program running on the microcontroller was developed using Arduino Integrated Development Environment (IDE) with C programming language. The range of functionality of the system is wide, it is implemented with low cost hardware, simple user interface, high security reliability and theft alert are some of the major advantages of this project. It is intended that the fingerprint lock safe shall eventually replace the manual traditional methods used for personal safe keeping of properties that is common in Nigeria and hence provide practicable way for a better security.